(untitled) (Annals of Medical Research, 2021)
Aim: We aimed to investigate the relationship between chronotype and depression schemas and sensitivity to depression in healthy medical students with sensitivity and cognitive scales.Materials and Methods: The study included 38 healthy fifth-year medical students enrolled in Van Yuzuncu Yil University Medical Faculty. All the participants were administered a sociodemographic background questionnaire, followed by the Morningness-Eveningness Questionnare (MEQ), the Dysfunctional Attitude Scale (DAS), and the Leiden Index of Depression Sensitivity-Revised (LEIDS-R).Results: The average total MEQ score was 51.60 ± 8.71. No significant correlation was found between total DAS score total LEIDS-R score (p: 0.5847; r: 0.09154) and LEIDS-R type (p: 0.9081, r: 0.01936). Both MEQ type and total MEQ score established a significant correlation with the ‘perfectionism’ parameter on LEIDS-R. Moreover, the correlation between total MEQ score and ‘perfectionism’ was at a moderate level (p: 0.0014, r: 0.50021), it indicated that the level of perfectionism increases with the increase in the tendency towards morningness.Conclusion: No relationship was found between chronotype and tendency to depression among medical students. It was determined that the perfectionism scheme was strengthened with the increasing tendency towards the morningness. Hypothetically, the hyperactivation of morning-type features can be a protective factor against depression.